Walteriella n. g. (Monogenoidea: Dactylogyridae) from the gills of pimelodid catfishes (Siluriformes: Pimelodidae) from the Peruvian Amazonia based on morphological and molecular data - Mendoza-Palmero, Carlos A; Mendoza-Franco, Edgar F; Acosta, Aline A; Scholz, Tomáš (Systematic parasitology, 2019)
On the basis of morphological and molecular data, Walteriella n. g. is proposed to accommodate the dactylogyrid parasites Walteriella conica n. sp. (type-species) from the gills of Platynematichthys notatus (Jardine) (type-host) and Brachyplatystoma juruense (Boulenger), and Walteriella ophiocirrus n. sp. from the gills of Platystomatichthys sturio (Kner) (type-host), all fish host belonging to the Pimelodidae collected in the Peruvian Amazonia. Species of the new genus are distinguished from other dactylogyrids infecting Neotropical catfishes by the presence of a folded germarium, a male copulatory organ basally articulated to the accessory piece, a cone-shaped seminal receptacle, and ventral and dorsal bars with projections directed anteriorly. Both species of the new genus form a strongly supported lineage closely related to Dactylogyridae gen. sp. 13, a parasite of Hypophthalmus edentatus Spix & Agassiz (Pimelodidae) in an analysis of partial sequences of the 28S rRNA gene. The clade formed by species of Walteriella n. g. and Dactylogyridae gen. sp. 13 is closely related to other dactylogyrids infecting pimelodid catfishes. Based on the morphology of its haptoral elements and copulatory complex, the species Dactylogyridae gen. sp. 13 is morphologically different from species of Walteriella n. g., but its generic assignment is still unclear.
Keywords: Peru; Catfishes; Phylogeny; RNA ribozomální 28S; druhová specificita; Gills; Animals; Species Specificity; sumci; žábry; RNA, Ribosomal, 28S; zvířata; fylogeneze; Trematoda